2021
DOI: 10.1101/2021.03.01.433418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A ciliopathy complex builds distal appendages to initiate ciliogenesis

Abstract: Cells inherit two centrioles, the older of which is uniquely capable of generating a cilium. We identified that three evolutionarily conserved proteins that underlie human ciliopathies, CEP90, MNR and OFD1, form a complex. This complex localized to both distal centrioles and centriolar satellites, proteinaceous granules surrounding centrioles. Cells and mice lacking CEP90 or MNR did not generate cilia, failed to assemble distal appendages, and did not transduce Hedgehog signals. Disrupting the satellite pools … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 66 publications
10
20
1
Order By: Relevance
“…The search of proximity partners of FOPNL in mammalian cells led us to identify CEP90. As expected from previous results, we identified in our mass spectrometry MNR/OFIP in proximity of FOPNL (Chevrier et al, 2016), (Kumar et al, 2021). Interestingly, these two proteins are working in a complex with OFD1 to build a cilium (Lopes et al, 2011a).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The search of proximity partners of FOPNL in mammalian cells led us to identify CEP90. As expected from previous results, we identified in our mass spectrometry MNR/OFIP in proximity of FOPNL (Chevrier et al, 2016), (Kumar et al, 2021). Interestingly, these two proteins are working in a complex with OFD1 to build a cilium (Lopes et al, 2011a).…”
Section: Discussionsupporting
confidence: 88%
“…This discrepancy might be due to the fact that these authors used 5-ethynyl-29-deoxyuridine (EdU) to distinguish the different phases of the cell cycle, while we used unsynchronized U2OS cells. Another possibility is that the recruitment of the complex differs between cell types causing this difference between our study (Kumar et al, 2021) which used RPE1 cells. Consistent with our findings, numerous distal end proteins such as C2CD3, CP110, Centrin2 (Thauvin-Robinet et al, 2014), (Kleylein-Sohn et al, 2007), (Paoletti et al, 1996) have already been observed on newly born procentrioles.…”
Section: The Ternary Complex Points Out the Future Position Of Distal Appendages Assemblymentioning
confidence: 96%
See 3 more Smart Citations